(untitled) (Jurnal Kemanusiaan, 2019)
Based on previous reports, there are complaints from industries that our engineering graduates lack in non-technical skills. The engineers that are freshly entered the industry are not industry-ready due to lack of required non-technical skills. One of the reason is when they are still undergarduates, they receive minimum industry exposure during their industrial training. Furthermore, most of them have less industry experience and non-technical that is expected by today’s industry. Unfortunately, some students undergo industrial training to the industry which is not relevance to what they are studied before. This problem contributes to unemployment issue among engineering fresh graduates. This paper presents a study on sixteen engineering graduates from various public universities in Malaysia on effects of industrial training programme to them. A semi-structured interview was used to gain data from the respondents. The results reveal that 90% of respondents which underwent only 2.5 to 3 months of industrial training did not satisfy with the short duration of training. In addition, 43.75% of them claimed that the industries that they had been placed are not related to their courses.